Przekroje struktury kosztów w publicznych uczelniach akademickich w Polsce - Ćwiąkała-Małys, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
Payment costs with mark-ups have the biggest share in the cost structure of public high schools in Poland. Payment costs were increasing during the whole analysing period, i.e. from 2001 to 2006. The analysis reveals that payment costs with mark-ups in 2006 were 58.7% higher than in 2001. The cost analysis using different sections provides a useful tool in the management of public money for both the ministry and a public high school.
Keywords: publiczne szkolnictwo wyższe; koszty